Evaluation of the anti-nociceptive potential of ethanolic extract of leaves of Bryophyllum pinnatum in experimental animals - Handique, Chimi; Dutta, Arijit; Lahkar, Mangala (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The plant Bryophyllum pinnatum is traditionally used for the treatment of pain and inflammation. The present study was carried out to evaluate the antinociceptive effect of the ethanolic extract of the leaves of B. pinnatum (EEBP) using a hot plate method and acetic acid induced writhing test in mice. Methods: In the hot plate analgesiometer method, the time between the placement on the hot plate and the occurrence of licking of the paws, shaking or jumping off from the plate was recorded as response latency. Total numbers of stretching episodes for 30 mins immediately after acetic acid injection in all the groups were recorded in acetic acid induced writhing method. Pentazocine (10 mg/kg intraperitoneal) and aspirin (500 mg/kg) were used as the standard drugs in the hot plate and acetic acid induced writhing method, respectively. Extract was used in 200, 300 and 400 mg/kg doses. Results: At all the three doses the EEBP showed significant (p<0.01) anti-nociceptive activity in experimental models of Eddy’s hot plate analgesiometer and acetic acid induced writhing method in mice. Conclusion: The observed pharmacological activities provide the scientific basis to support traditional claims, as well as exploring some new and promising leads in the management of pain.